Forecasting the price of Research Octane Number 97 (RON97) in Malaysia: a Box-Jenkins approach - Mohd Zaki, Nurul Syakinah; Mohamed Yusof, Noreha (Academica Press Solutions, 2025)
In Malaysia, there are three types of gasoline which are Diesel, RON95 and RON97. In this study, the focus will be RON97. RON97 is one of the factors that can significantly impact Malaysia’s economy. This fuel also has many factors that influence the price of it, which in turn affect both consumer and user. Consumers, businesses, policymakers, and energy industry players in Malaysia rely on accurate RON97 price forecasts for effective budgeting, cost management, economic planning, and strategic decision-making. The volatile nature of global crude oil prices, together with the influence of taxes, refining costs, and currency exchange rates, makes RON97 price prediction a complex challenge. This study addresses the need to determine the best forecasting model for monthly fuel price of RON97 between Box-Jenkins autoregressive integrated moving average (ARIMA) models. The data is taken from Malaysia’s Official Open Data Portal, which consists of the price of Petroleum and Diesel in Malaysia. This data consists of monthly prices of RON97 fuel in Malaysia since January 2020 until January 2024. The ARIMA (1,1,1) model was selected as the best forecasting approach. The forecasted range of the price of RON97 generated by this model was between RM 3.37 and RM 3.62. Future research could investigate the use of external factors or seasonal components to improve model performance.